Corporate Governance in Listed Firms: Does Market Competition Make a Difference? - Le Thi Thoan; Vo Thi Ngoc Thuy (Asian Academy of Management Journal, 2024)
This study assesses the relationship between market competition and corporate governance by analysing 562 non-financial companies listed on the Vietnamese stock market from 2010 to 2019. We used the quantitative method through oridinary least squares (OLS) robust and feasible generalised least squares (FGLS) regression to control heteroscedasticity and autocorrelation, which is suitable with panel data to test the above relationship. According to the research results, market competition has complementary and alternative effects on corporate governance, as reflected in the positive and negative effects of the variable Herfindahl-Hirschman Index (HHI), a proxy for market competition, on corporate governance. Market competition has a support impact on corporate governance, which is more evident in board size, CEO duality, and CEO ownership. In contrast, the impact of market competition substituted corporate governance and reduced the role of corporate governance, as demonstrated by the independent board members. As a result, our study provides an extended understanding of the factors affecting corporate governance, primarily based on contingency theory. Furthermore, this study provides evidence for further research in this field and identifies a number of potential solutions for investors and regulators.